Conservative surgery of the ovary - Polto, Jaime J (Cirugía del Uruguay, 1973)
The author anal:¡,zes conservative ovarían surgery in the majority of gynecological surgery cases, with specíal emphasis on cases of ovarian tumors. Therapy is also indicated. Ovarían functions include prevention of arteriosclerosis and, fundamentally, coronary diseases. The author recommends: -In surgery of benign processes of ttterus, preservation of ovaries if healthy and non atrophíc, regardless ot age. -In surgery of tubes due to fallopian pregnancies, ovaries may be preserved if no other pathology in found thereín. -In ovarían surgery, emphasis is laid on the importance of residual ovarían pathology following abscission of benign ovarian tumors. Generally speaking in cases of ovarían cysts conservative procedures are advisable when the patíent is under 40 years of age; after this, complementary radical surgery should be performed accompanied by administration of estrogens. The paper includes discussion of the rare cases in which it is possible to act conservatively in the presence of malign ovarían tumors.